2021
DOI: 10.35683/jcm1914e.104
|View full text |Cite
|
Sign up to set email alerts
|

Influence of entrepreneurial orientation on organisational performance : evidence from Congolese Higher Education Institutions

Abstract: Background: Land based casinos are facing growing competition from other gambling modes like online gaming, which is a major concern for the future of this industry. The designing of new slot machine games are therefore critical, particularly as the life cycles of these games become shorter. Rapid technological changes in both online and land-based casinos, all contribute to the shortening lifespan of slot-machine games. With that said, game developers needs to stay on top of new technologies in order to shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This chapter builds on the SHAPE project-supported research supported in part by the National Research Foundation of South Africa (Grant Number: 122002-Shape). These works include: Adelakun and Van der Westhuizen (2021), Awotunde and Van der Westhuizen (2021a), Awotunde and Van der Westhuizen (2021b), IGI Global (2020), Nhleko and van der Westhuizen (2022), Ruba et al (2021), Van der Westhuizen (2017a), Van der Westhuizen (2017b), Van der Westhuizen (2018a), Van der Westhuizen (2018b), Van der Westhuizen (2019), Van der Westhuizen (2021).…”
Section: Discussionmentioning
confidence: 99%
“…This chapter builds on the SHAPE project-supported research supported in part by the National Research Foundation of South Africa (Grant Number: 122002-Shape). These works include: Adelakun and Van der Westhuizen (2021), Awotunde and Van der Westhuizen (2021a), Awotunde and Van der Westhuizen (2021b), IGI Global (2020), Nhleko and van der Westhuizen (2022), Ruba et al (2021), Van der Westhuizen (2017a), Van der Westhuizen (2017b), Van der Westhuizen (2018a), Van der Westhuizen (2018b), Van der Westhuizen (2019), Van der Westhuizen (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Product and service innovation is the creation of different new products and services by upgrading the quality of current products and services in order to improve customer experience and customer satisfaction (Lumpkin and Dess 1996;Singh and Hanafi 2020;Ruba et al 2021). Moreover, technology innovativeness is defined as the company's orientation towards embracing new working techniques, processes, tools, and skills (Covin and Wales 2012;Lechner and Gudmundsson 2014;Rauch et al 2009).…”
Section: Innovativenessmentioning
confidence: 99%
“…Innovativeness (INN) is one of the main components of company strategic orientation (Gomes et al 2022;Ruba et al 2021). Strategic orientation is the set of specific "paths" or principles of strategic management that determine the internal processes of a company to help it adapt to environmental conditions in order to improve its performance (Bubenik et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, entrepreneurial orientation, knowledge management, and strategy implementation have a significant effect on improving Islamic boarding school performance. Ruba et al (2021) conducted research to analyze the relationship between entrepreneurial orientation and organizational performance in Congolese higher education institutions. The study's findings demonstrate that each dimension of entrepreneurial orientation makes a unique contribution to the understanding of organizational performance.…”
Section: Relationship Between Entrepreneurial Orientation and Organiz...mentioning
confidence: 99%
“…The existing literature on the relationship between organizational learning capability, entrepreneurial orientation, and organizational performance has yielded inconclusive results. The studies conducted by Alosani (2020), Al-Dhaafri et al (2016), Rofiaty (2019), andRuba et al (2021) collectively establish that there exists a notable correlation between entrepreneurial approach and the performance of public sector companies. In the study conducted by Balasubramanian et al (2020), it was shown that there is no statistically significant relationship between entrepreneurial orientation and organizational performance.…”
Section: Introductionmentioning
confidence: 99%